Coordinated Induction of Antimicrobial Response Factors in Systemic Lupus Erythematosus - Ayyappan, Prathapan; Harms, Robert Z.; Buckner, Jane H.; Sarvetnick, Nora E. (Frontiers in Immunology, 2019)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease characterized by dysregulated autoantibody production and complement activation leading to multi-organ damage. The disease is associated with increased intestinal permeability. In this study, we tested the hypothesis that SLE subjects have increased systemic exposure to bacteria. Since bacteria induce the expression of antimicrobial response factors (ARFs), we measured the levels of a series of clinically relevant ARFs in the plasma of SLE subjects. We found that levels of sCD14, lysozyme and CXCL16 were significantly elevated in SLE subjects. A strong positive correlation was also observed between sCD14 and SELENA-SLEDAI score. Interestingly, the ratio of EndoCAb IgM:total IgM was significantly decreased in SLE and this ratio was negatively correlated with sCD14 levels. Although, there were no significant differences in the levels of lipopolysaccharide binding protein (LBP) and fatty acid binding protein 2 (FABP2), we observed significant positive correlations between lysozyme levels and sCD14, LBP, and FABP2. Moreover, Galectin-3 levels also positively correlate with lysozyme, sCD14, and LBP. Since our SLE cohort comprised 43.33% males, we were able to identify gender-specific changes in the levels of ARFs. Overall, these changes in the levels and relationships between ARFs link microbial exposure and SLE. Approaches to reduce microbial exposure or to improve barrier function may provide therapeutic strategies for SLE patients.